2017
DOI: 10.15421/191713
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility in tax reporting

Abstract: UDC classification: 330.1, 330.8, 330.3 JEL classification: H26, H32Purpose -to describe a compliance-monitoring equilibrium in presence of compatibility costs in a setting when managers and other parties have different attitude towards compliance. Design/Method/Approach. Classical game theory -Nash equilibrium. Findings. If compatibility costs are small, there exist a unique stable Nash equilibrium of the game between the tax authority and a population of heterogeneous firms. In this equilibrium, the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 6 publications
0
10
0
3
Order By: Relevance
“…GRW (1986) made a significant advance to the game model by introducing the dynamic games of tax evasion that involve law enforcement, whereby the opportunistic decision to evade taxes is influenced by parameters such as fine or audit costs. The GRW model has been further extended and applied in other studies (Andreoni et al, 1998; Lipatov, 2005, 2006, 2008). In this line, a vast tax enforcement literature emerges to understand the effects of deterrence and compliance on tax evasion (Andreoni et al, 1998; Braithwaite & Braithwaite, 2001).…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…GRW (1986) made a significant advance to the game model by introducing the dynamic games of tax evasion that involve law enforcement, whereby the opportunistic decision to evade taxes is influenced by parameters such as fine or audit costs. The GRW model has been further extended and applied in other studies (Andreoni et al, 1998; Lipatov, 2005, 2006, 2008). In this line, a vast tax enforcement literature emerges to understand the effects of deterrence and compliance on tax evasion (Andreoni et al, 1998; Braithwaite & Braithwaite, 2001).…”
Section: Research Backgroundmentioning
confidence: 99%
“…Many studies uphold the effect of fines in dissuading tax evasion, that is, the application of high fines increases the cost of evasion and, thus, reduces the rate of evasion (Bayer & Cowell, 2009; Lipatov, 2006). Studies have also found that the effect of the fines depends crucially on the accounting standard adopted by the agents.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Mais uma vez pode-se auferir a baixa correlação entre os percentuais de multas aplicados pelos órgãos fiscalizadores e a sonegação fiscal. Mostrando possíveis interações entre agentes sonegadores, Lipatov (2006) evidenciou que o efeito dos percentuais de multas dependerá crucialmente do padrão contábil 1113 adotado pelos agentes. Se o padrão contábil escolhido for do tipo agressive, 1 2 14 o aumento no percentual de multas pode ter efeito adverso na fiscalização.…”
Section: Gráfico 1 -Relação Entre T E H -L Dos Países Selecionadosunclassified
“…Embora as informações sejam restritas, ampliar os grupos de países estudados pode fornecer informações de maior robustez para os parâmetros. Como sugestão para trabalhos futuros, recomenda-se utilizar as extensões aos modelos Lipatov (2006;, juntamente com os dados disponíveis e realizar o estudo de forma empírica.…”
Section: Considerações Finaisunclassified
See 1 more Smart Citation